Research on Low Carbon Consumption Intention Survey and Incentive Mechanism under the Dual Carbon Goal - Li, Wenyu; Wang, Yanli (International Journal of Global Economics and Management, 2024)
In order to explore residents' low carbon consumption intention, this paper constructs a model of the influencing factors of low carbon consumption willingness through multiple linear regression with the help of planning behavior theory, and studies the incentive mechanism of carbon credits according to the model results. The results show that low carbon consumption behavior attitude, subjective norm and perceptual behavior control all have a positive impact on low carbon consumption intention, and the three independent variables can explain 77.1% of the changes in the dependent variable, among which perceptual behavior control has the greatest impact. Based on the results of the model, this paper briefly studies the incentive mechanism of carbon credits, and finally puts forward some reasonable suggestions for low carbon consumption based on the actual situation, so as to actively respond to and promote low carbon consumption actions.